Tinjauan Arsitektur Lanskap pada Ruang Luar Sekolah Alam: Studi Kasus SD Alam Muhammadiyah Golf Banjarbaru - Nahla Rusiani (Universitas Medan Area, 2026)
This study aims to review the application of landscape architecture principles in the outdoor environment of SD Alam Muhammadiyah Golf Banjarbaru as a nature-based primary education setting. The main objective of this research is to assess the compatibility of outdoor spatial planning with contextual learning concepts, thermal comfort, and environmental sustainability. The study employs a qualitative descriptive method through field observation, visual documentation, and zoning analysis based on educational, ecological, and recreational functions. The findings indicate that the school’s outdoor environment demonstrates a well-designed green layout incorporating natural landscape elements such as shade vegetation, open play areas, educational gardens, and natural walking paths that support active outdoor learning activities. The outdoor space not only complements indoor learning but also serves as an educational medium that fosters ecological awareness and social interaction among students. Nevertheless, improvements are still needed in pedestrian circulation, rainwater management, and the integration between indoor and outdoor learning spaces to achieve a balance between functional and ecological aspects. This study provides a conceptual foundation for developing environmentally friendly outdoor learning environments that are adaptive to tropical climates and support sustainable nature-based education.